Electrospinning of poly(vinylpyrrodine) template for formation of ZrO2 nanoclusters for enhancing properties of composite proton conducting membranes - Nasef, M. M. (Taylor & Francis Group, LLC, 2017)
Nanosized ZrO2 clusters were prepared by electrospinning a poly(vinylpyrrodine) (PVP)/ZrO2 mixture for calcination to remove PVP template and sizing. The morphological, chemical, structural, and thermal resistance changes during preparation stages were investigated using scanning electron microscope, energy-dispersive X-ray spectroscopy, transmission electron microscope, X-ray diffraction, and thermogravimetric analysis. The obtained ZrO2 clusters were used for preparation of nanocomposite membranes by dispersion in 2,6-pyridine polybenzimidazole (2,6-Py-PBI) matrix at 5 wt% content followed by phosphoric acid (PA) doping. The ZrO2 nanoclusters were found to be uniformly distributed in 2,6-Py-PBI/PA matrix leading to a remarkable increase in the PA doping level and proton conductivity of the obtained composite membrane.